A Simple Proposal for a "Debt-Sensitive Stability Pact" - Francesco Saraceno; Paola Monperrus-Veroni (Vierteljahrshefte zur Wirtschaftsforschung, 2004)
The main rationale for fiscal policy rules is the concern for long-term sustainability of public finances, that in a monetary union may affect the other members. Among many other criticisms, the Stability and Growth Pact (SGP) has been seen as contradictory or incomplete because it focuses on deficit rather than debt, the main indicator of public finances' soundness. Furthermore, the few references to debt that were present in the treaties and related regulations are essentially ignored in actual practices. Some of the reform proposals that came out lately have addressed the issue and tried to embed a debt criterion in the Pact. We review these proposals and put forward our own proposed modification: the deficit ratio countries should target is weighted by their relative debt. With respect to the other proposals taking into account debt, our own has the advantages of simplicity, symmetry, and low arbitrariness. To make it politically acceptable to high debt countries, nevertheless, could require to set the targets, at least initially, at level higher than the Maastricht criteria. – – Das Hauptargument für fiskalpolitische Regeln ist die Berücksichtigung der langfristigen Nachhaltigkeit der öffentlichen Finanzen, die in einer Währungsunion andere Mitgliedstaaten berührt. Neben anderen Punkten wird am Stabilitäts- und Wachstumspakt (SWP) kritisiert, dass er widersprüchlich oder unvollkommen sei, da der Fokus auf dem Defizitkriterium liegt und nicht auf dem Schuldenstand. Die in den Verträgen zu findenden wenigen Verweise auf den Schuldenstand werden praktisch ignoriert. Einige spät veröffentlichte Reformverschläge tragen allerdings dem Schuldenstandskriterium Rechnung und versuchen, dies in den SWP aufzunehmen. Im vorliegenden Aufsatz wird vorgeschlagen, das Defizitkriterium mit dem Schuldenstand zu gewichten. Der Vorschlag ist einfach, symmetrisch und nicht arbiträr. Um den Vorschlag für Länder mit hohem Schuldenstand attraktiv zu machen, müssten zumindest zu Beginn die Ziele für sie über dem Maastricht-Kriterium liegen dürfen.
Keywords: 330; Öffentliche Schulden; Eurozone; EU-Staaten; Europäischer Stabilitätsmechanismus